IMPLEMENTASI SEKOLAH BEBAS BULLYING PADA ANAK USIA DINI MELALUI KOMUNIKASI POSITIF GURU - Sakti, Syahria Anggita; Widyastuti, Titik Mulat (UNIVERSITAS SLAMET RIYADI, 2020)
The goal of this research is to explain how to implement bullying-free schools in Surya Marta Kindergarten Yogyakarta and also to understand the coordination that discusses the application of school bullying through positive teacher communication. This research uses qualitative. Subjects of research are principals, teachers, and students' parents. Data collection is done through observation, interview, and collection techniques. While data analysis uses data reduction, displaying data, and making conclusions. Data validity technique with source triangulation. The results showed how the implementation of bullying-free schools through positive communication of teachers at Surya Marta Kindergarten Yogyakarta was applied in the form of activities that involved: (1) improving two-way communication between schools with research on victims and bullying through parenting activities; (2) each student guardian meeting is held a special agenda concerning the meeting and resolution of the intimidation case; (3) formation of a supervisory board; (4) Test the value of harmony and cooperation in the subject matter. The following: (1) parents of students do not fully understand the material delivered by the school; (2) receiving media which contains antibullying at school; (3) the absence of specific program implementation manuals. Abstrak Penelitian ini bertujuan untuk menjelaskan bagaimana implementasi sekolah bebas bullying di TK Surya Marta Yogyakarta dan permasalahan apa saja yang dihadapi dalam penerapan sekolah bebas bullying melalaui komunikasi positif guru. Penelitian ini menggunakan pendekatan kualitatif. Subjek penelitian meliputi kepala sekolah, guru, dan orang tua siswa. Pengumpulan data yang dilakukan lewat teknik observasi, wawancara, dan dokumentasi. Sedangkan analisis data menggunakan reduksi data, display data, dan penarikan kesimpulan. Teknik keabsahan data dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa implementasi sekolah bebas bullying melalui komunikasi positif guru di TK Surya Marta Yogyakarta diaplikasikan ke berbagai bentuk aktivitas yaitu diantaranya: (1) meningkatkan komunikasi dua arah antara pihak sekolah dengan orangtua korban dan pelaku bullying melalui kegiatan parenting; (2) setiap pertemuan wali murid diadakan agenda khusus tentang pembahasan dan penekanan terhadap kasus bullying; (3) pembentukan dewan pengawas; (4) memperkuat nilai kerukunan dan kerja sama dalam materi pelajaran. Adapun kendalanya meliputi: (1) orang tua siswa belum sepenuhnya memahami materi yang sekolah sampaikan; (2) kurangnya media yang berisi tentang program anti bullying di sekolah; (3) tidak adanya buku acuan khusus pelaksanaan program.